Управління бізнес-процесами і стартап-студіями підприємств інтернет-торгівлі: оцінка конкурентоспроможності інновацій та інформаційного потенціалу - Перерва, Петро Григорович; Кобєлєва, Тетяна Олександрівна; Шеін, Євген Сергійович; Нечепоренко, Денис Анатолійович (Чорноморський національний університет імені Петра Могили, 2026)
У статті досліджено теоретико-методичні засади управління бізнес-процесами підприємств інтернет-торгівлі в умовах цифровізації. Особливу увагу приділено функціонуванню стартап-студій як інноваційних структур, що забезпечують серійне створення та масштабування нових бізнес-моделей. Обгрунтовано необхідність комплексного підходу до оцінки конкурентоспроможності інноваційних рішень, що впроваджуються в електронній комерції. Розроблено науково-методичний підхід до оцінювання інформаційного потенціалу підприємства як базового ресурсу для оптимізації бізнес-процесів та підвищення ринкової стійкості. Доведено, що синергія ефективного управління стартап-проєктами та повноцінного використання інформаційних активів є визначальним фактором формування стратегічних конкурентних переваг на ринку інтернет-торгівлі. Запропоновано систему критеріїв та показників оцінки конкурентоспроможності інновацій та інформаційного потенціалу підприємств інтернет торгівлі. Результати дослідження демонструють, що конкурентоспроможність підприємств інтернет торгівлі визначається здатністю інтегрувати процесне управління з інноваційною гнучкістю стартап студій, ефективно використовувати інформаційний потенціал та забезпечувати системну підтримку інноваційних рішень.

The article presents a comprehensive study of the theoretical and methodological foundations of business process management in e-commerce enterprises under the conditions of digital economic transformation. Particular attention is paid to the functioning of startup studios as innovative organizational structures that ensure systematic and serial creation of new business models, their rapid testing, and scaling in the e-commerce market. It is shown that startup studios act as catalysts of innovative activity, creating an environment for the integration of entrepreneurial ideas, technological solutions, and managerial practices. The necessity of applying a comprehensive approach to assessing the competitiveness of innovative solutions is substantiated, taking into account not only economic indicators but also organizational, technological, and informational aspects. A scientific and methodological toolkit has been developed for evaluating the informational potential of an enterprise as a fundamental resource that determines the effectiveness of business process optimization, adaptability, and long-term market resilience. Informational potential is considered as a set of data, knowledge, digital technologies, and managerial competencies that ensure strategic flexibility and innovative dynamics of the enterprise. It is proven that the synergy of effective startup project management and the full utilization of informational assets is a key factor in forming strategic competitive advantages in the field of ecommerce. A system of criteria and indicators for assessing the competitiveness of innovations and informational potential is proposed, including financial performance, scalability speed, level of technological integration, quality of managerial decisions, and the ability to build partnership ecosystems. The research results demonstrate that the competitiveness of e-commerce enterprises is determined by their ability to integrate process management with the innovative flexibility of startup studios, effectively utilize informational potential, and provide systemic support for innovative solutions.
Business process management and startup studios of e-commerce enterprises: assessing the competitiveness of innovations and information potential
Keywords: інтернет-торгівля; інформаційні технології; моделі оцінювання; конкурентоспроможність; управління; цифровізація; бізнес-процеси; стартап-студії; інформаційний потенціал; e-commerce; information technologies; evaluation models; competitiveness; management; digitalization; business processes; startup studios; informational potential